2011
DOI: 10.4174/jkss.2011.80.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of Meckel's Diverticulum by a Chicken Bone; Preoperatively Presenting as Bowel Perforation

Abstract: Perforation of Meckel's diverticulum by foreign bodies is an extremely rare cause of acute abdomen in adults. We report a case of perforated Meckel's diverticulum by a chicken bone with localized abdominal abscess in a 46-year old man. The patient had been brought to the hospital with fever, abdominal pain and abdominal distention. On computed tomography, the mass-like lesion was considered to be an abdominal abscess caused by perforated bowel due to a suspicious foreign body. Resection of a segment of ileum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…According to Chae et al [7], perforation is rarely seen and was reported as being responsible for 0.5% of symptomatic diverticulum. Another study (composed of 12 men and 11 women, with a mean age of 42.6 years, over a 15-year period) concluded that diverticulum-related complications demonstrated by surgery were inflammation in 14 patients, bleeding in 5 patients, intestinal obstruction in 3 patients, and penetrating foreign body causing perforation in 1 patient [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Chae et al [7], perforation is rarely seen and was reported as being responsible for 0.5% of symptomatic diverticulum. Another study (composed of 12 men and 11 women, with a mean age of 42.6 years, over a 15-year period) concluded that diverticulum-related complications demonstrated by surgery were inflammation in 14 patients, bleeding in 5 patients, intestinal obstruction in 3 patients, and penetrating foreign body causing perforation in 1 patient [3].…”
Section: Discussionmentioning
confidence: 99%
“…Perforation is very rarely seen and, in a review, was reported as being responsible for 0.5% of symptomatic diverticulum [4][5][6]. In adult patients, intestinal obstruction is the most common complication, with incidence rates varying from 22 to 50% [7].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of Meckel’s diverticula contain heterotopic mucosa, of which over 60% consist of gastric mucosa [1]. Other heterotopic tissues include pancreatic tissue, which is found in 6% of cases, jejunal, duodenal mucosa or Brunner’s glands, with every one of this type found in 2% of cases, and pancreatic islets, colonic mucosa, endometriosis and hepatobiliary tissue, which are found in smaller percentages [2]. A commonly quoted ‘rule of twos’ also applies: 2% of the population have the anomaly, it is approximately 2 inches in length, it is usually found within 2 feet proximal to the ileocecal valve, it is often found in children under two years of age, it contains two types of common ectopic tissue (gastric and pancreatic) and it affects males twice as often as females [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, perforation of Meckel's diverticulum by a foreign body is one complication which has received comparatively little attention, perhaps owing to its rarity and, in a review, was reported as being responsible for 0.5% of symptomatic diverticula. [2]. In this article, we report a case of perforation of Meckel's diverticulum by a chicken bone with a brief review of the relevant literature and record a further case of this occurrence to the very few reported cases which can be found in the world literature.…”
Section: Introduction:-mentioning
confidence: 96%
“…[1] Though Meckel's diverticulum remains mostly asymptomatic throughout life with an overall lifetime complication rate of approximately 4%. [2], complications of surgical importance such as bleeding (11.8%) intestinal obstruction (36.5%), inflammation (12.7%), intussusceptions (13.7%) and neoplasm (3.2%) have been described and commented on in previous literature. However, perforation of Meckel's diverticulum by a foreign body is one complication which has received comparatively little attention, perhaps owing to its rarity and, in a review, was reported as being responsible for 0.5% of symptomatic diverticula.…”
Section: Introduction:-mentioning
confidence: 99%